Progress and prospects of research and application of X80 pipeline steel and steel pipe in China - Yaorong FENG; Lingkang JI; Weiwei LI; Yinglai LIU; Chunyong HUO (You-qi chuyun, 2020)
With the rapid development of oil and gas pipeline construction, X80 pipeline steel and steel pipe have been applied on large scale. The research and application history and main progress of X80 high-grade pipeline steel and steel pipe in China were reviewed, the challenges faced were pointed out, and the suggestions for development were put forward. After nearly 20 years of development, about 17 000 km of X80 oil and gas transmission pipelines have been constructed, with the single pipeline capacity up to 380×108 m3/a. China's X80 pipe manufacturing and pipeline construction technology have also ascended to the ranks of international leaders. Key technologies such as microstructure analysis, identification and assessment, strength test and yield to tensile ratio control, fracture and deformation control of X80 pipeline steel and steel pipe have been formed, as well as manufacturing technologies related to the X80 hot-rolled coiled sheet and large diameter thick wall spiral submerged arc welding pipe, wide and thick plate and large-diameter thick-wall longitudinal submerged arc welding pipe, high strain pipeline steel and steel pipe, and the design and manufacturing of induction bends and fittings. These technologies have strongly supported the construction of major pipeline projects like Line 2 of West-to-East Gas Pipeline Project and the China-Russia Eastern Gas Pipeline Project. For future development, the following suggestions were put forward. It was suggested to strengthen the weldability assessment and control of coiled sheet or steel plate, deepen the research on field welding technology and quality performance control, promote the application of high-grade pipeline steel and steel pipes in the construction of large-capacity pipelines, and improve the research and application of theory and technology on failure control and integrity of oil and gas pipeline.